2017
DOI: 10.21775/cimb.024.059
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Viral Metagenomic Extraction Methods

Abstract: A crucial step in the molecular detection of viruses in clinical specimens is the efficient extraction of viral nucleic acids. The total yield of viral nucleic acid from a clinical specimen is dependent on the specimen's volume, the initial virus concentration and the effectiveness provided by the extraction method. Recent Next Generation Sequencing (NGS)-based diagnostic approaches (i.e. metagenomics) provide a molecular 'open view' into the sample, as they theoretically generate sequence reads of any nucleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…To date, few studies have assessed the impact of different extraction methods on the performance of metagenomics. Klenner et al evaluated four manual QIAamp nucleic acid extraction kits (QIAamp Viral RNA Mini Kit, QIAamp DNA Blood Mini Kit, QIAamp cador Pathogen Mini Kit, and QIAamp MinElute Virus Spin Kit) with four different viruses (including Reovirus , Orthomyxovirus , Orthopoxvirus , and Paramyxovirus ), and reported that the selection of the kits has only a minor impact on the yield of viral reads and the quantity of reads obtained by NGS [ 28 ]. However, this study only evaluated manual kits from the same manufacturer and with separate RNA and DNA extraction methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, few studies have assessed the impact of different extraction methods on the performance of metagenomics. Klenner et al evaluated four manual QIAamp nucleic acid extraction kits (QIAamp Viral RNA Mini Kit, QIAamp DNA Blood Mini Kit, QIAamp cador Pathogen Mini Kit, and QIAamp MinElute Virus Spin Kit) with four different viruses (including Reovirus , Orthomyxovirus , Orthopoxvirus , and Paramyxovirus ), and reported that the selection of the kits has only a minor impact on the yield of viral reads and the quantity of reads obtained by NGS [ 28 ]. However, this study only evaluated manual kits from the same manufacturer and with separate RNA and DNA extraction methods.…”
Section: Discussionmentioning
confidence: 99%
“…While there are many manual and automatic extraction methods available, it is important to choose the most sensitive and reliable one for mNGS. Numerous studies evaluating different extraction platforms in terms of their viral qPCR performance have found that the choice of extraction platform has a major impact on the reliability of the diagnostic results [ 24 , 25 , 26 , 27 , 28 , 29 ]. Furthermore, nucleic acid extraction methods can also impact bacteriome profiles [ 30 , 31 , 32 ] as well as the detection of particular viruses with mNGS [ 16 , 23 , 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The assay efficiency curve was 101.94% showing that the results are highly reliable, and the standard curve can be used for an absolute quantification of the viral genome. In addition, the melting curve showed a unique peak at 79.03 °C that could be used to confirm ChPV in a sample, and therefore avoid false-negative results in tissue samples with interfering DNA, such as thymus, spleen, bursa, and blood [ 33 , 34 ]. Hence, in the present study, ChPV was detected and quantified in the enteric contents of broilers, laying hens, and breeders using the fast-qPCR based on the SYBR Âź Green assay that had been reported in previous studies [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specimen DNA extraction for viral pathogen materials and human tissues was as previously described [17]. The extraction of viral RNA and the storage of sample material were critical, as viral RNA integrity affected qPCR sensitivity and specificity.…”
Section: Methodsmentioning
confidence: 99%